2021
DOI: 10.1111/trf.16499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leukoreduction and temperature on risk of bacterial growth in CPDA‐1 whole blood: A study of Escherichia coli

Abstract: Background Collection of non‐leukoreduced citrate‐phosphate‐dextrose‐adenine (CPDA‐1) whole blood is performed in walking blood banks. Blood collected under field conditions may have increased risk of bacterial contamination. This study was conducted to examine the effects of WBC reduction and storage temperature on growth of Escherichia coli (ATCC® 25922™) in CPDA‐1 whole blood. Methods CPDA‐1 whole blood of 450 ml from 10 group O donors was inoculated with E. coli. Two hours after inoculation, the test bags … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…The effect of storage on hematological parameters confirmed the results from other studies on CPDA‐1 whole blood, 17–20 with stable hemoglobin and hematocrit, and a decrease in platelet count and WBC count. Aggregates prevented accurate counting of platelets in two of the test bags, one on day 7 and one on day 35.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The effect of storage on hematological parameters confirmed the results from other studies on CPDA‐1 whole blood, 17–20 with stable hemoglobin and hematocrit, and a decrease in platelet count and WBC count. Aggregates prevented accurate counting of platelets in two of the test bags, one on day 7 and one on day 35.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, a recent study showed that the presence of WBCs might be beneficial if the blood is stored is stored at higher temperatures. 17 In conclusion, repeated transient exposure of coldstored CPDA-1 whole blood to 28°C for a 4-h period followed by a return to 4°C once a week over a 35-day period did not have any notable negative impact on the measured quality parameters and hemostatic function. The effect on hemolysis beyond three cycles over 21 days was uncertain and warrants further investigation.…”
Section: S110mentioning
confidence: 67%
See 1 more Smart Citation
“…Bacteria that resist immune clearance prior to WB leukoreduction, may not necessarily proliferate during cold storage as recently shown by Braathen et al [15]. In their study, Escherichia coli , which was not fully eliminated before WB leukoreduction, did not replicate during storage at 2–6°C.…”
Section: Introductionmentioning
confidence: 54%
“…Bacteria that resist immune clearance prior to WB leukoreduction, may not necessarily proliferate during cold storage as recently shown by Braathen et al [15]. In their study, Escherichia coli, which was not fully eliminated before WB leukoreduction, did not replicate during storage at 2-6 C. However, the safety risk posed by bacteria able to proliferate in CWB (i.e., psychrotrophic) was described by James and Stocks in 1957 [16].…”
Section: Introductionmentioning
confidence: 58%